PENGARUH MODEL TEAM ASSISTED INDIVIDUALIZATION DENGAN STRUCTURE EXERCISE METHOD TERHADAP HASIL BELAJAR - Syah, Fanny Firman; Widodo, Antonius Tri; Nurhayati, Sri (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2014)
This study aimed to investigate the differences of learning outcomes between students with learning Team Asissted Individualization (TAI) and Structure Exercise Method (SEM) equipped with student worksheet, students with simply TAI learning, and students without TAI and SEM models, and which the implementation of model is the best ones that can be used as an alternative better model. Experimental design of this study is a pretest and posttest control group design. Samples were taken with cluster random sampling technique. Based on the analysis the average cognitive achievement test of experimental class I is 84.67, experimental class II is 82.41, and control class is 76.61. The Anova testÂ results showed the average difference is significant between the three classes. Scheffes post-ANOVA test showed the average difference is significant between each class and demonstrated that the experimental class I is the class with the best learning outcomes. The contribution of aplication of TAI and SEM models is 20,82%. Affective and Psychomotor learning outcomes of TAI and SEM class showed that it is the best result from three class. The conclusion of this study that learning TAI and SEM equipped with student worksheet produce the best learning outcomes.Keywords: Learning Outcomes, Structure Exercise Method, Team Assisted Individualization